Artificial Intelligence Applications and Innovations: Day-to-Day Life Impact - João M. F. Rodrigues; Pedro J. S. Cardoso; Marta Chinnici (Applied Sciences, 2023)
The idea of an intelligent machine has fascinated humans for centuries [...]